2001
DOI: 10.1021/jo0106795
|View full text |Cite
|
Sign up to set email alerts
|

Highly E-Selective and Effective Synthesis of Antiarthritic Drug Candidate S-2474 Using Quinone Methide Derivatives

Abstract: We have developed an efficient and E-selective synthesis of an antiarthritic drug candidate (E)-(5)-(3,5-di-tert-butyl-4-hydroxybenzylidene)-2-ethyl-1,2-isothiazolidine-1,1-dioxide (S-2474; 1), in which alpha-methoxy-p-quinone methide is used as a key intermediate. alpha-Methoxy-p-quinone methide was revealed to be an equivalent to a p-hydroxy protected benzaldehyde. It reacts smoothly with alpha-sulfonyl carbanion to give 1,6-addition intermediates, which can be further processed to provide S-2474 directly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Also, a SciFinder search revealed that 2,6-di-tert-butyl-4-(methoxymethylene)cyclohexa-2,5-dienone (the methyl enol ether of 5) was a solely documented example, derived from the dearomatization-enolization-methylation of 3,5-di-tert-butyl-4-hydroxybenzaldehyde due to the highly sterically hindered structure. 12 With the oxidation reaction conditions in hand, we next compared the oxidations of 2-bromo-4-cresol (1a), 4-cresol (1b) and 2-methoxy-4-cresol (1c), in order to evaluate the aforementioned approaches (Scheme 2). As displayed in Scheme 5, compared to 1a, the unsubstituted and electron-neutral 4-cresol 1b delivered the desired 4-hydroxybenzaldehyde (2b) in a relatively low yield of 81%, along with the dimer 6b (6% yield) and undeterminable tars derived from undesired couplings.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a SciFinder search revealed that 2,6-di-tert-butyl-4-(methoxymethylene)cyclohexa-2,5-dienone (the methyl enol ether of 5) was a solely documented example, derived from the dearomatization-enolization-methylation of 3,5-di-tert-butyl-4-hydroxybenzaldehyde due to the highly sterically hindered structure. 12 With the oxidation reaction conditions in hand, we next compared the oxidations of 2-bromo-4-cresol (1a), 4-cresol (1b) and 2-methoxy-4-cresol (1c), in order to evaluate the aforementioned approaches (Scheme 2). As displayed in Scheme 5, compared to 1a, the unsubstituted and electron-neutral 4-cresol 1b delivered the desired 4-hydroxybenzaldehyde (2b) in a relatively low yield of 81%, along with the dimer 6b (6% yield) and undeterminable tars derived from undesired couplings.…”
Section: Resultsmentioning
confidence: 99%
“…While all three compounds were prepared according to published synthetic routes, the hydrolytic instability of QM-OMe required recrystallization prior to each test. We observed a 10% conversion to 3,5-di- tert -butyl-4-hydroxybenzaldehyde when crystalline QM-OMe is stored for 24 h under nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to use, styrene was passed over alumina to remove the TBC that is packaged with the product. 2-(3,5-Di- tert -butyl-4-oxocyclohexa-2,5-dien-1-ylidene)­acetonitrile ( QM-CN ), 2,6-di- tert -butyl-4-(methoxymethylene)­cyclohexa-2,5-dienone ( QM-OMe ), , and 4-benzylidene-2,6-di- tert -butylcyclohexa-2,5-dienone ( QM-Ph ) were prepared according to previous literature reports. Due to its hydrolytic instability, QM-OMe had to be recrystallized from hexanes immediately prior to each use to remove 3,5-di- tert -butyl-4-hydroxybenzaldehyde generated during storage …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the E -selectivity did not seem to be controlled by the thermodynamic factor of the products. We focused on the unique character of the phenol derivative which easily forms the quinone methide . Dehydration of 12 proceeded even using 1 mol equiv of NaHCO 3 with E -selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The overall yield was only 19.8%. Another synthetic route was developed by Inagaki et al using a quinone methide derivative as an equivalent of the protected p -hydroxybenzaldeyde derivative (Scheme ) . It required four reactions and the overall yield rose to 71.2%.…”
Section: Introductionmentioning
confidence: 99%